2013
DOI: 10.3892/ol.2013.1555
|View full text |Cite
|
Sign up to set email alerts
|

A new perspective of vasculogenic mimicry: EMT and cancer stem cells (Review)

Abstract: Vasculogenic mimicry (VM), a new pattern of tumor microcirculation, is important for the growth and progression of tumors. Epithelial-mesenchymal transition (EMT) is pivotal in malignant tumor progression and VM formation. With increasing knowledge of cancer stem cell (CSC) phenotypes and functions, increasing evidence suggests that CSCs are involved in VM formation. Recent studies have indicated that EMT is relevant to the acquisition and maintenance of stem cell-like characteristics. Thus, in this review we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
114
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(121 citation statements)
references
References 111 publications
(133 reference statements)
6
114
0
Order By: Relevance
“…Discussion VM, the ability of tumor cells to undergo vessel formation de novo, has been described in multiple cancers (reviewed in .......................................................................................................................... Fan et al 6 ). Findings from previous studies show that VM is associated with aggressive tumors and poor patient prognoses.…”
Section: Blocking Cxcr2 Receptor Signaling Impairs Proliferation and mentioning
confidence: 99%
See 2 more Smart Citations
“…Discussion VM, the ability of tumor cells to undergo vessel formation de novo, has been described in multiple cancers (reviewed in .......................................................................................................................... Fan et al 6 ). Findings from previous studies show that VM is associated with aggressive tumors and poor patient prognoses.…”
Section: Blocking Cxcr2 Receptor Signaling Impairs Proliferation and mentioning
confidence: 99%
“…[7][8][9] Indeed, a number of studies revealed that angiogenesis inhibitors did not significantly affect VM, thus underscoring the need for improved antivascular therapies that specifically target VM. 6,10,11 Transgelin (also known as SM22a and TAGLN) is an early marker of smooth muscle cell differentiation and is an actin-binding protein that affects cytoskeletal dynamics by stabilizing actin filaments. The association between transgelin and the cytoskeleton accounts for its involvement in cancer-related processes such as proliferation, migration, invasion, and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular mechanisms underlying VM remain unclear; nevertheless, tumor cells lining VM networks secrete matrix metalloproteinases (MMP) and express vascular endothelial (VE)-cadherin to induce extracellular matrix (ECM) remodeling (4,5). Our previous studies also showed that VM occurs in HCC (6) and that EMT may be involved in VM formation in HCC (7). Previous research data indicated that VM was observed in 18 out of 97 patients with HCC (19%; ref.…”
Section: Introductionmentioning
confidence: 96%
“…The epithelial-mesenchymal transition (EMT) is a process implicated in drug resistance, metastasis and the generation of CSCs (21,31,32). The present study analyzed the mRNA and protein expression of the EMT markers E-cadherin and N-cadherin in pancreatic cancer cells treated with thalidomide.…”
Section: Discussionmentioning
confidence: 99%